(untitled) (Research, Society and Development, 2022)
The so-called Divorce Amendment was imperative in bringing considerable changes to constitutional family law. One of the main ones to be mentioned, undoubtedly, is the amendment given to Art. 226, § 6, of the 1988 Constitution, which was responsible for giving rise to an eminent discussion among legal scholars and its operators about the institute of judicial separation, which still persists. However, the decision affects REsp 1.247.098 – MS clarified considerable doubts regarding the new constitutional article 226, § 6, and it is inappropriate to ignore the considerations presented in the appeal judged by the STJ. In this way, a detailed study of this decision is made, using a qualitative approach on the subject, with due consideration to the lessons found in better doctrine, previous jurisprudence and, obviously, in ordinary and constitutional. At the beginning, a contextual and historical view of Constitutional Amendment 66 is given, only then to search for the most relevant arguments of the winning vote and the losing vote of the decision under analysis and, thus, give a solution to the raised problem. In fact, a complete view of the judgment is sought to guide the discussion about the permanence or not of judicial separation in national law. The conclusions reached by the work were in the sense that, certainly, there is room for the institute of separation of law in the Brazilian legal system.